La prescripción de la acción de la administración aduanera para el cobro de obligaciones tributarias y su regulación en el Código Orgánico De La Producción, Comercio e Inversiones - Carrión Sempértegui, Diego Xavier (2015)
Trade between the different country, through their border areas, is regulated and controlled by the customs administration, which in its activities must be guided unerringly to the constitutional principles of public administration, including mainly the efficiency, administrative simplification and revenue adequacy. In reviewing the Organic Code of Production, we can see that this provides for a too long time to operate the prescription of the action of the customs administration to collect tax obligations, as well as for claims that may be filed by concept undue payment or overpayment by the taxpayer. These terms contravene the principle of legal certainty, and make excessively prolonged uncertainty about the legal link generated from the obligation. Therefore to study this legal problem, this work was developed called "PRESCRIPTION OF THE ACTION OF THE CUSTOMS ADMINISTRATION FOR THE COLLECTION OF TAX OBLIGATIONS AND REGULATION ON ORGANIC PRODUCTION CODE". The study includes a comprehensive collection in the conceptual theoretical, doctrinal, legal and comparative law field, as well as results that were obtained through the opinions of lawyers, which serve to realize some conclusions and recommendations, and end with the approach of a legal proposal to reform the Organic Code of Production Trade and Investment, made for the purpose of limitation periods that the action for recovery can exercise tax administration and for filing claims by administered, are appropriate to the constitutional principles of Ecuador's tax regime